Four Quadrant Control of Battery Operated Vehicle - Sindhu P; Narayanan K (Journal of Power Electronics and Devices, 2016)
In present scenario attitude towards climate and CO2 emissions has accelerated the use of electric and hybrid vehicles. So IC engines are replaced by electric motor with battery as a source. This project deals with a chopper based dc drive for battery operated vehicle. The objective of the project are, to implement a control circuit for a class-E chopper (suitable for 4-Q operation) fed separately excited dc motor in order to ensure bidirectional control, to improve the performance of vehicle by conserving energy during regenerative braking and to ensure fast control of dc motor. The speed of separately excited dc motor can be varied from below and up to rated speed in a closed loop control system using class E chopper as a converter in MATLAB simulation. Class-E chopper has 4 control switches- S1, S2, S3 & S4 and 4 diodes- D1, D2, D3 & D4. The chopper firing circuit receives appropriate duty cycle (δ) from control circuit and then chopper provides variable voltage across the armature of the motor for achieving desired speed. There are two control loops in the control circuit, one for controlling current and another for speed. Switching pulse is generated for the switches in the converter as per the switching sequence of forward motoring, forward braking, reverse motoring and reverse braking.